Land valuation in support of responsible land consolidation on Ghana's rural customary lands. Issue 361 (4th July 2018) - Asiama, Kwabena Obeng; Bennett, Rohan; Zevenbergen, Jaap; Asiama, Seth Opuni
Abstract : In this paper, we develop a framework for an approach that assigns values to customary rural farmland parcels based on the local people's view of land value to support land consolidation. In a case study of Nanton, Ghana, key land value factors were identified and weighted by the local community. The weights were integrated into the framework that produced a Land Value Index for each farmland parcel. Though the strength of the approach is found in scenario and sensitivity analyses. However, the prime weakness of this framework is that it is more expensive to use than automatic valuation models.